MIMO Radar Waveform Design for Spectrum Sharing with Cellular Systems A MATLAB Based Approach - Khawar, Awais; Abdelhadi, Ahmed; Clancy, Charles; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses spectrum sharing between cellular systems and radars. The book addresses a novel way to design radar waveforms that can enable spectrum sharing between radars and communication systems, without causing interference to communication systems, and at the same time achieving radar objectives of target detection, estimation, and tracking. The book includes a MATLAB-based approach, which provides reader with a way to learn, experiment, compare, and build on top of existing algorithms.
Introduction -- BPSK Radar Waveform -- QPSK Radar Waveform -- Appendix A: Solution of Waveform Design Optimization Problem -- Appendix B: MATLAB Code for Waveform Design.
Keywords: Telecommunication; Electric power production; Communications Engineering, Networks; Electrical Power Engineering; Microwaves, RF Engineering and Optical Communications